2015
DOI: 10.1002/nme.4899
|View full text |Cite
|
Sign up to set email alerts
|

An unsymmetric 4-node, 8-DOF plane membrane element perfectly breaking through MacNeal's theorem

Abstract: Summary Among numerous finite element techniques, few models can perfectly (without any numerical problems) break through MacNeal's theorem: any 4‐node, 8‐DOF membrane element will either lock in in‐plane bending or fail to pass a C0 patch test when the element's shape is an isosceles trapezoid. In this paper, a 4‐node plane quadrilateral membrane element is developed following the unsymmetric formulation concept, which means two different sets of interpolation functions for displacement fields are simultaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 70 publications
(125 reference statements)
1
65
0
Order By: Relevance
“…After successful development of plane 4-node, 8-DOF quadrilateral element US-ATFQ4 [45] which can break through the limitation defined by MacNeal [6,7], a new 3D 8-node hexahedral element US-ATFH8…”
Section: Discussionmentioning
confidence: 99%
“…After successful development of plane 4-node, 8-DOF quadrilateral element US-ATFQ4 [45] which can break through the limitation defined by MacNeal [6,7], a new 3D 8-node hexahedral element US-ATFH8…”
Section: Discussionmentioning
confidence: 99%
“…Nodes 1, 2, 3, and 4 are the corner nodes; ( t x I , t y I ) and ( t S I , t T I ) are respectively the Cartesian coordinates and quadrilateral area coordinates (QACM‐II) (see Appendix A) of the corner node I ( I = 1, 2, 3, 4) at time t ; and u αI is the α ‐component ( α = 1, 2) of the displacement increments at node I . For the unsymmetric element US‐ATFQ4, 2 different sets of interpolation functions for displacement fields are simultaneously used. The first set is for the virtual displacement fields { δ u } and employs the shape functions of the traditional 4‐node bilinear isoparametric element, ie, {}δboldu={}δuxδuy=[]boldNtrue‾{}δnormalΔqe, where {}δnormalΔqe=δux1δuy1δux2δuy2δux3δuy3δux4δuy4T, []boldNtrue‾=[]trueN10Ntrue‾20Ntrue‾30Ntrue‾400Ntrue‾10Ntrue‾20Ntrue‾30Ntrue‾4, with …”
Section: Extension Of the Unsymmetric 4‐node 8‐dof Plane Element Us‐mentioning
confidence: 99%
“…The second set is for the real incremental displacement fields { u } and adopts a composite coordinate interpolation scheme with analytical trial functions {}u={}uxuy=[]P{}α=[]11em0tx1em0ty1em0tU71emtU801em101emtx01emtytV71emtV8{}α1α2α3α8, where α i ( i = 1 ∼ 8) are 8 undetermined coefficients; t U 7 , t V 7 , t U 8 , and t U 8 are the linear displacement solutions for plane pure bending in arbitrary direction and in terms of the second form of quadrilateral area coordinates (QACM‐II) ( S , T ) (see Appendix A) at time t . The detailed expressions of t U 7 , t V 7 , t U 8 , and t U 8 are derived in the work of Cen et al and given in Appendix B. Substitution of nodal coordinates (including Cartesian and QACM‐II) and nodal displacement increments into Equation yields {}u={}uxuy=[]0pttboldNtrue^{}normalΔqe, where {}normalΔqe=centerux1…”
Section: Extension Of the Unsymmetric 4‐node 8‐dof Plane Element Us‐mentioning
confidence: 99%
See 1 more Smart Citation
“…An important work related to the development of distortion insensitive plane elements was proposed by Chen et al By applying the natural quadrilateral area coordinates, several 4‐node, 8‐node nonconforming plane membranes were formulated, in which AGQ6‐I and AGQ6‐II were the most representative ones. It is reported that these elements can produce results with high numerical precision in distorted mesh and were free of trapezoidal locking.…”
Section: Introductionmentioning
confidence: 99%